No gaussianidad primordial en la perturbación en la curvatura en el escenario del curvatón (2007)
In the very successful and alternative model to the inflaton scenario, “the curvaton model”, two scalar fields are present during inflation: one, the inflaton, is in charge of generating and controlling the inflationary period, and another, the curvaton, is in charge of generating the primordial curvature perturbation ζ which in turn gives origen to the formation of large-scale structures in the Universe. The observed ζ is highly Gaussian, but the current satellite experiments, like NASA’s WMAP, search for a possible small deviation from the exact gaussianity. In this paper we will study the bispectrum Bζ (k1, k2, k3) of ζ in the curvaton scenario, whose normalisation fNL gives information about the level of non-gaussianity in ζ. This study will be done by making use of the δN formalism. We will explicitely state the advantage of this formalism and give an expression for fNL in the curvaton scenario.